SUN-210 Testosterone Replacement Therapy Implicated in Osteonecrosis - Yang, Almira (J Endocr Soc, 2019)
Background Testosterone is indicated for men demonstrating testosterone deficiency clinically and biochemically(1). One of the possible adverse effects of testosterone is an increased risk of venous thromboembolism (VTE) especially in those with an underlying thrombophilia(2). Excessive Factor VIII activity is a common, but often underrecognized cause of hypercoagulability(3). Similarly, a less acknowledged manifestation of hypercoagulability may be osteonecrosis(4). We present a patient who developed osteonecrosis of the hip while on testosterone replacement therapy (TRT) and later found to have excessive Factor VIII activity. Clinical Case A 47-year-old male with past medical history of diabetes mellitus type 2, hyperlipidemia, obstructive sleep apnea compliant with continuous positive airway pressure device, non-smoker, presented for evaluation of secondary hypogonadism and TRT. Total testosterone was 229.7 ng/dL and free testosterone was 3.86 ng/dL at 9 AM. LH was 3.8 mIU/mL, and FSH was 5.6 mIU/mL. He had multiple complaints including reduced libido and sexual activity. Prolactin, TSH and salivary cortisol were within normal limits. Iron saturation was low. He was started on TRT. Total testosterone increased to 746.6 ng/dL. Approximately one year after TRT was started, he experienced persistent left hip pain. MR of the left hip revealed focal avascular necrosis involving the femoral head. He denied prior corticosteroid use, heavy alcohol use and prior hip injury. The patient has no known personal or family history of coagulopathy. A hypercoagulable work-up was completed and patient was found to have Factor VIII activity of 179% and 175% on repeat. He discontinued testosterone therapy. Fortunately, with the discontinuation of TRT and initiation of anticoagulation therapy, his osteonecrosis remained stable. Conclusion This case raises the question of whether patients should be screened for coagulopathies prior to TRT. One study found that of 16 cases of osteonecrosis after TRT, 4 (25%) had high (>150%) Factor VIII levels versus 7 of 103 (7%) healthy control subjects (P=.04)(5). Clinicians should be mindful when prescribing TRT given the potential increased risk for VTE including osteonecrosis. References 1) Bhasin et al. Guidelines for Testosterone Therapy in Men. J Clin EndocrinolMetab. 2018;103(5):1715-1744. 2) Martinez, C. et al. Testosterone treatment and risk of venous thromboembolism:population based case-control study. BMJ. 2016; 355:i5968. 3) Bobrow, R. Excess Factor VIII: A Common Cause of Hypercoagulability. J AmBoard Fam Pract. 2005;18(2):147-9. 4) Lykissas, M. et al. The role of hypercoagulability in the development ofosteonecrosis of the femoral head. Orthopedic Reviews. 2012;4:e17. 5) Glueck CJ et al. Testosterone Therapy Can Interact With Thrombophilia, Leadingto Osteonecrosis. Orthopedics. 2015;38(12):e1073-8.